DIGITAL TECHNOLOGIES IN MARKETING ACTIVITY DIAGNOSTICS (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article examines the interpretation of various foreign and domestic economic concepts of “marketing activity diagnostics” and “marketing digitalization”. It is considered the leading software for solving marketing tasks and performing marketing activity diagnostics. It studies how using modern digital platforms ensures the adoption of sound strategic decisions that increase companies' competitiveness.The purpose of the article. Consideration of interpretations by various foreign and domestic scientists of economic concepts: «diagnostics of marketing activities», «digitalization of marketing». Research into the impact of digital technologies on the diagnostics of companies' marketing activities. Disclosure of the main advantages of using digital technologies in marketing diagnostics.Metods. The research used content analysis, comparative analysis, and logical generalization. The methodological basis of the research was theoretical provisions on marketing activities, scientific works of famous economists in the field of marketing, and digital technologies.Results. The essence of the economic concept of «diagnostics of marketing activities» and «digitalization of marketing» is revealed. The study showed that using advanced technologies, such as web analytics, AI, Big Data, and CRM systems, provides companies with competitive advantages and makes informed management decisions. In the future, the role of digital technologies in marketing diagnostics will only decrease, requiring companies to be flexible, adaptable, and innovative in their approach to analyzing marketing processes.Conclusiоns. Digital marketing analytics is a critical step for companies looking to improve their advertising and customer engagement. Innovative solutions such as Big Data analytics, marketing automation, and competitive intelligence tools enable companies to make strategically informed decisions and achieve better results.
Keywords: marketing diagnostics; marketing; digital technologies; digitalization; marketing analysis.